Genomic dissection of Australian Bordetella pertussis isolates from the 2008–2012 epidemic. Issue 4 (April 2016) - Safarchi, Azadeh; Octavia, Sophie; Wu, Sunny Z.; Kaur, Sandeep; Sintchenko, Vitali; Gilbert, Gwendolyn L.; Wood, Nicholas; McIntyre, Peter; Marshall, Helen; Keil, Anthony D.; Lan, Ruiting
Summary: Objectives: Despite high pertussis vaccination coverage, Australia experienced a prolonged epidemic in 2008–2012. The predominant Bordetella pertussis genotype harboured pertussis toxin promoter allele, ptxP3, and pertactin gene allele, prn2 . The emergence and expansion of prn non-expressing isolates (Prn negative), were also observed. We aimed to investigate the microevolution and genomic diversity of epidemic B. pertussis isolates. Methods: We sequenced 22 B . pertussis isolates collected in 2008–2012 from two states of Australia which are geographically widely separated. Ten of the 22 were Prn negative isolates with three different modes of silencing of prn ( prn ::IS 481 F, prn ::IS 481 R and prn ::IS 1002 ). Five pre-epidemic isolates were also sequenced for comparison. Results: Five single nucleotide polymorphisms were common in the epidemic isolates and differentiated them from pre-epidemic isolates. The Australian epidemic isolates can be divided into five lineages (EL1–EL5) with EL1 containing only Prn negative isolates. Comparison with global isolates showed that three lineages remained geographically and temporally distinct whereas two lineages mixed with isolates from 2012 UK outbreak. Conclusion: Our results suggest significant diversification and the microevolution of B. pertussis within the 2008–2012 Australian epidemic. Highlights: Single nucleotide polymorphisms play an important role in the microevolution of the Australian 2008–2012 epidemic B. pertussis . The Australian 2008–2012 epidemic B. pertussis isolates can be divided into five lineages with spatial and temporal clustering of isolates. The same mechanism of inactivation of the prn gene can occur independently.